2017
DOI: 10.4172/2472-016x.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Lymphoma Mimicking as Osteomyelitis: An Unusual Presentation

Abstract: Primary Bone Lymphoma is a rare disorder, even though secondary involvement of bone marrow in systemic Lymphoma is common. Most of Primary Bone Lymphomas are Primary Bone Diffuse Large B-cell Lymphomas. We describe a case of Primary Bone Lymphoma, initially treated as Osteomyelitis of unknown etiology. This case shows the difficulties that can occur while diagnosing this entity. We provide an overview of Clinical, Radiological, Pathological characteristics of these rare tumours along with review of Literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are a number of case reports in the literature where the PBL mimicked subacute and chronic osteomyelitis and was treated as osteomyelitis [ 7 - 10 ]. The rarity of the disease and the misleading histopathological and imaging features placed PBL last on the list of our differential diagnoses for a 32-year-old male patient with insidious onset pain, intermittent fever, and diffuse and tender swelling with normal X-ray and non-specific MRI features.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of case reports in the literature where the PBL mimicked subacute and chronic osteomyelitis and was treated as osteomyelitis [ 7 - 10 ]. The rarity of the disease and the misleading histopathological and imaging features placed PBL last on the list of our differential diagnoses for a 32-year-old male patient with insidious onset pain, intermittent fever, and diffuse and tender swelling with normal X-ray and non-specific MRI features.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we report a 34-year-old man who presented progressive hip pain and osteolytic bone lesions. He was later diagnosed with primary diffuse large B-cell bone lymphoma, and previous studies had also suggested that osteomyelitis unusually mimics PB-DLBCL [5][6][7] Several rationales led us to believe that the previous workup session was insufficient, and another approach is needed to be taken. Hence, we decided to perform an open biopsy.…”
Section: Discussionmentioning
confidence: 99%